PERANCANGAN DAN PEMBUATAN APLIKASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE PROCESS COSTING PADA TOKO HANâS BAKERY - Rismadewi, Inneke; Setiawan, Alexander; Purnama, Christian (Jurnal Infra, 2013)
A store which is engaged in the production of bread, Hans Bakery Shop currently has no system to calculate the cost of production. In the absence of cost calculations, then the store can not know how these productions. And there is no record of raw materials and how materials are issued at the time of production. Based on the background of the problems that the designed system to calculate the Cost of Production to overcome these problems. The process of system design applications through several stages, the first survey of production systems, analyzing data and designing systems using the Data Flow Diagram and Entity Relationship Diagram. Database created by using Microsoft SQL Server 2005. Applications created with Microsoft Visual Studio 2005. NET.Results obtained from the application that has been made, among others, can save raw materials, bread recipes, customer data, transaction ordering raw materials, sales transactions, sales order transactions, the report card stock, and so on.From the test results, a program created to process administrative data on Hans Bakery shop to produce a report that has been able to meet the needs of stores that run more effectively and efficiently.